Optimal Commitment Strategy of the Wind-battery-hydrogen Hybrid System in the Spot Market - Zhang, Ru (Business Management and Strategy, 2025)
In this paper, we consider the problem of making the advance power commitments for the wind farms and the hydrogen supply plan for the hydrogen spot market, in the presence of the hybrid energy storage system with battery based and hydrogen based, mean-reverting price pocesses of power and hydrogen and the auto regressive energy generation process from winds, which extends the model in (Kim & Powell, 2011) and (Finnah & Gönsch, 2021). The problem is solved with dynamic programming algorithm with backward induction and the infinite horizon analysis. We obtained an optimal energy commitment policy and an optimal hydrogen supply plan under the above assumptions, which are indeed the extensions of the conclusion in (Kim & Powell, 2011) and (Finnah & Gönsch, 2021). Finally the property of stationary process of the hybrid storage levels corresponding to the optimal policy and plan are proved.